Ethanol-induced CYP2E1 Expression is Reduced by Lauric Acid via PI3K Pathway in HepG2 Cells - Ying-Huan Lua,; Wei-Wah Ong,; Hong-Kin Wong ,; Choy-Hoong Chew, (Tropical Life Sciences Research, 2020)
The metabolism of alcohol involves cytochrome P450 2E1 (CYP2E1)-induced oxidative stress, with the association of phosphatidylinositol-3-kinases (PI3K) and nuclear factor kappa B (NF?B) signalling pathways. CYP2E1 is primarily involved in the microsomal ethanol oxidising system, which generates massive reactive oxygen species (ROS) and ultimately leads to oxidative stress and tissue damage. Lauric acid, a major fatty acid in palm kernel oil, has been shown as a potential antioxidant. Here, we aimed to evaluate the use of lauric acid as a potential antioxidant against ethanol-mediated oxidative stress by investigating its effect on CYP2E1 mRNA expression and the signalling pathway in ethanol-induced HepG2 cells. HepG2 cells were firstly treated with different concentrations of ethanol, and subsequently co-treated with different concentrations of lauric acid for 24 h. Total cellular RNA and total protein were extracted, and qPCR and Western blot was carried out. Ethanol induced the mRNA expression of CYP2E1 significantly, but lauric acid was able to downregulate the induced CYP2E1 expression in a dose-dependent manner. Similarly, Western blot analysis and densitometry analysis showed that the phosphorylated PI3K p85 (Tyr458) protein was significantly elevated in ethanol-treated HepG2 cells, but co-treatment with lauric acid repressed the activation of PI3K. However, there was no significant difference in NF?B pathway, in which the normalised NF?B p105 (Ser933) phosphorylation remained constant in any treatment conditions in this study. This suggests that ethanol induced CYP2E1 expression by activating PI3K p85 (Tyr458) pathway, but not the NF?B p105 (Ser933) pathway in HepG2 cells.